Gestão por competências: estudo sobre mapeamento do perfil de competências dos servidores técnico-administrativos em educação da Universidade Tecnológica Federal do Paraná Campus Campo Mourão - Cavalheiro, Daniela (2023)
Social transformation and the complexity of its processes on a global scale are changing the way the public sector works and are presenting new challenges for everyone involved in the public sphere. Dealing with new ways of working presupposes civil servants who are prepared to work in complex and demanding environments in terms of knowledge, skills and attitudes. The public sector needs to create flexible and adaptable organizations that have the capacity to be innovative and transformative. In this context, competency-based management has been identified as an alternative management tool to the instruments traditionally used in organizations. This model emerges to align human skills to generate and sustain organizational strategies. And it proposes to guide efforts to plan, capture, develop and evaluate, at the different levels of the organization (individual, collective and organizational), the skills necessary to achieve its objectives. As a starting point, the mapping of competences constitutes the main managerial tool for recognizing the skills present in the organization. Furthermore, through this diagnosis, the institution can identify its skills gap, that is, the discrepancy between the skills needed to implement the corporate strategy and the skills available internally. Thus, this research aims to present a study on the profile of Technical-Administrative servants in Education at the Federal Technological University of Paraná Campus Campo Mourão to propose a mapping of competences. This tool will subsidize the implementation of the competency-based management model in the development and training of civil servants, in line with the institutional objectives described in the UTFPR Institutional Development Plan (PDI). The analysis intends to enhance qualification actions based on the collective construction of institutional actions, as well as assist in making strategic decisions, generating public value in the delivery of quality services by organizations of this nature.